PELATIHAN PENGOLAHAN HASIL PETERNAKAN DI KELOMPOK IBU-IBU PKK - ,, Paulini; Anjalani, R.; Rumbang, N. (Buletin Udayana Mengabdi; Vol 22 No 4 (2023): Buletin Udayana MengabdiDO - 10.24843/BUM.2023.v22.i04.p07, 2023)
The implementation of the Community Empowerment Assistant Lecturer Program (PDPPM) was implemented in a group of PKK women in Bawan Village, Banama Tingang District, Pulang Pisau Regency, Central Kalimantan Province. The potential for developing a business for processing livestock products in Bawan Village is very large, especially processing eggs and chicken meat which are very popular among the community, especially children. The objectives of this activity were: (1) PKK women are able to produce processed food products from livestock to support food security in households and communities; (2) Empowering rural women to support food security and increase household income; (3) Can develop small businesses in Bawan Village through the role of women who can meet local and regional demands; and (4) Making Higher Education institutions a source of information and development of science and technology. The method for implementing PDPPM community service activities consists of: (1) Preparation, through socialization activities and location surveys; (2) Training on processing livestock products; (3) Assistance during community service activities; and (4). Evaluation carried out at the end of the training activity. After carrying out the counseling and training activities the group of mothers were able to make and process livestock products into nutritious food, such as salted eggs and nuggets made from chicken meat with mixed ingredients consisting of vegetables, so that children who do not like to consume vegetables can consume it. In addition, they can sell the products they produce and increase their family income. Keywords: Processing technology, livestock products, PKK women's group, Bawan Village.